2017
DOI: 10.1177/0042098017714212
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to homeownership among young professionals in urban China: The role of family resources

Abstract: Studies on China’s new housing regime primarily focus on state and market as major provision mechanisms and the role of family assistance is largely ignored. This paper explores how family resources help Chinese young professionals in their pathways to homeownership by drawing on qualitative interviews done in Beijing. It was found that young professionals who managed to secure parental help usually came from middle-class families, with parents who were public-sector professionals and managers benefiting from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…Although no prior research has directly explored the link between class and housing in China, previous studies have shown that class plays an important role in housing outcomes in many Western capitalist countries (Kurtz & Blossfeld, 2004). Moreover, some existing research findings lend support to the idea that class structure is associated with housing outcomes (Or, 2018). As the privatised housing market in urban China has started resembling the housing market in other capitalist countries, I expect that the following hypotheses: Hypothesis 3: Net of other covariates, class structure exerts a statistically significant effect on homeownership among workers in transitional urban China.…”
Section: Class Structure and Housing In Urban Chinamentioning
confidence: 82%
See 1 more Smart Citation
“…Although no prior research has directly explored the link between class and housing in China, previous studies have shown that class plays an important role in housing outcomes in many Western capitalist countries (Kurtz & Blossfeld, 2004). Moreover, some existing research findings lend support to the idea that class structure is associated with housing outcomes (Or, 2018). As the privatised housing market in urban China has started resembling the housing market in other capitalist countries, I expect that the following hypotheses: Hypothesis 3: Net of other covariates, class structure exerts a statistically significant effect on homeownership among workers in transitional urban China.…”
Section: Class Structure and Housing In Urban Chinamentioning
confidence: 82%
“…Other research extends the market transition debate to analyze the mechanisms of housing inequality in China (Fu & Lin, 2014;Huang & Clark, 2002;Or, 2018). Since urban China has completed the transition into a privatised housing market, some scholars who support the market-centred perspective argue that the market sector accounts for a greater share of housing supply and thus the state has become less important in determining housing outcomes (Song & Xie, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Li, Sato, and Sicular 2013). These parents were often public sector professionals and managers who had benefited from public housing privatization in the 1990s and later housing asset appreciation in the 2000s (Or 2018). Zhu (2018) argue that the intergenerational transmission of economic resources has contributed to the reproduction of housing and social inequalities in urban China, similar to what has been found in the West (Helderman and Mulder 2007).…”
Section: Accessibility Implicationsmentioning
confidence: 99%
“…Radical housing reforms over recent decades have greatly promoted the development of real estate in Chinese cities, and this has been accompanied by a rapid rise in housing prices. Young adults, who cannot benefit from the housing privatisation that assisted older generations and have not had enough time to accumulate wealth through the labour market, have consequently become more dependent on parental support to access homeownership (Cui, Deng, & Lu, 2019; Deng, Hoekstra, & Elsinga, 2016; Or, 2018; Zhang & Bian, 2019), which has come to represent the primary housing tenure suitable for family households. This became especially true after the implementation of the one‐child policy in the 1980s, as the younger generations, who are the only child in their family, are more likely to receive parental support (Song & Huang, 2011).…”
Section: Introductionmentioning
confidence: 99%